FOSTERING SUSTAINABLE ECONOMIC GROWTH THROUGH EXPORT EXPANSION (Academicia Globe: Inderscience Research, 2024)
This study comprehensively examines the pivotal role of foreign trade and trade liberalization in driving economic growth within Uzbekistan, a country undergoing significant economic transformation. As Uzbekistan gradually shifts from a controlled to a market-oriented economy, trade liberalization has emerged as a critical policy tool. This paper provides an in-depth analysis of Uzbekistan's trade policy reforms, examining their influence on various economic indicators, including GDP growth, employment rates, and sectoral productivity. By increasing market access, enhancing industrial efficiency, and promoting economic diversification, trade liberalization has facilitated Uzbekistan’s integration into the global economy.